ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERSALINAN PREMATUR DI RSUP NTB TAHUN 2013 - Linda Meliati (poltekkes kemenkes mataram, 2014)
Abstract: The incidence of preterm labor in the province General Hospital in 2012 amounted to 203 cases, increased to 369 cases in 2013 in NTB Province in 2012 infant death case 57/1000 live births is greater when compared with the results of Indonesia Demographic and Health Survey (IDHS ) in 2012, which is 32 deaths / 1,000 live births. The purpose of this study was to determine the factors - factors related to the incidence of preterm labor in the province in 2013 RSU type analytic study with cross sectional desaen. Entire population in this study who experienced maternal complications in labor amounted to 1534, the number of 317 samples, using a systematic random sampling technique sampling. The data used secondary data to search through medical records. Data were analyzed using univariate, bivariate chi-square test and multivariate analysis with multiple logistic regression. The results of the bivariate analysis study of 5 variables, 3 variables were significantly associated with the incidence of preterm birth parity (p value = 0.000), maternal illness (p value = 0.000), Gemelli (p value = 0.000), a variable that is not touch is the distance of pregnancy, fetal death in utero. The results of multiple logistic regression jointly obtained the greatest parity variables (dominant) influence on the cause of the occurrence of premature delivery (p = 0.000, OR = 1.749). Advice for health professionals is to maintain the quality of service of health workers, working always refers to the midwifery service standards have been determined.